Penindakan terhadap Pengemis Perspektif Yusuf Al Qaradhawi (Analisis Pasal 504 KUHP tentang Perbuatan Mengemis di Muka Umum) - Seva Maya Sari (Faculty of Sharia UIN Kiai Ageng Muhammad Besari Ponorogo, 2016)
This study aims to analyze and examine in depth the prosecution of beggars from the perspective of Yusuf Al Qaradhawi (analysis of article 504 of the Criminal Code on begging in public). This study is directed at library research with the primary data sources of the Criminal Code and Yusuf Al Qaradhawi's Musykilah al Faqr wa kaifa alajaha al Islam along with secondary data sources through literature review relevant to the problem under study. After the data has been collected and analyzed. Then the research results are obtained as follows: First, the activity of begging is qualified as a criminal offense in the field of public order as clearly regulated in Article 504 of the Criminal Code. This provision emphasizes that begging that can be subject to criminal sanctions is only begging carried out in public places. Second, Al Qaradhawi has a different view from the Criminal Code in taking action against beggars. The action is based on distinguishing the types of beggars, some are allowed and some are forbidden to beg. And he also suggests each way of overcoming it, for beggars who are forbidden, the authorities may give ta'zir, and for beggars who are allowed, the ways that can be taken include empowering zakat, infaq and alms properly and helping them get a job. Third, Al Qaradhawi's concept in taking action against beggars is in accordance with the complex needs of Indonesian society, so that the prospect of the future this concept can be made a reference in the reform of criminal law regarding action against beggars, because the problem of begging is increasingly complex and poverty is still a dominant factor that encourages begging.